2012
DOI: 10.1039/c2ra20518a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen storage performance for MgH2–NaAlH4 system—the effects of stoichiometry and Nb2O5 nanoparticles on cycling behaviour

Abstract: Nowadays, the technological utilization of reactive hydride composites (RHC) as promising hydrogen storage materials is hampered by their reaction kinetics. In the present work, effects of reactant stoichiometry on ensuing hydrogen sorption properties and pathway of the MgH 2 -NaAlH 4 (mole ratios 1 : 2, 1 : 1 and 2 : 1) system, both undoped and doped with Nb 2 O 5 nanoparticles, were investigated. It was found that the as-prepared reactant stoichiometry of MgH 2 /NaAlH 4 system had a profound impact on its de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…It is not clear yet why the reaction (6) was not observed in the NaAlH 4 eMgH 2 composites with the molar ratio of 1:1 [13,14] but only in the mixtures with excess MgH 2 [12,14]. Furthermore, the decomposition of the excess MgH 2 into Mg and hydrogen as well as reaction (4) take place.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is not clear yet why the reaction (6) was not observed in the NaAlH 4 eMgH 2 composites with the molar ratio of 1:1 [13,14] but only in the mixtures with excess MgH 2 [12,14]. Furthermore, the decomposition of the excess MgH 2 into Mg and hydrogen as well as reaction (4) take place.…”
Section: Introductionmentioning
confidence: 96%
“…The investigation of NaAlH 4 eMgH 2 [14] revealed two possible reaction schemes (1:4 and 1:2 vs. 1:1), unlike LiAlH 4 eMgH 2 (1:1, 1:2 and 1:4) [11]. The NaAlH 4 eMgH 2 (1:1) composition [13,14] is expected to form the dehydrogenation product Na 3 AlH 6 and follow the anticipated reactions (1), (2) and (4) [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of reactant stoichiometry on ensuing hydrogen sorption properties and pathway of the MgH 2 -NaAlH 4 (mole ratios 1:2, 1:1, and 2:1) system were investigated by Rafi-ud-din et al [21]. Variable temperature dehydrogenation data revealed that binary composites possessed enhanced hydrogen desorption properties compared with that of pristine NaAlH 4 and MgH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Despite these attractive properties, magnesium hydride (MgH 2 ) in its pure form is very stable and has very slow hydrogenation/dehydrogenation kinetics at temperatures less than 350 C. 8,9 Such serious drawbacks are considered as major barriers preventing the use of such an attractive metal hydride material for potential use in fuel cell applications. 10,11 Since the 1990s, enormous efforts have been dedicated for improving the hydrogenation/dehydrogenation behaviors of MgH 2 , using pure metal catalysts, 12,13 intermetallic compounds, 14 metal oxides, 15,16 carbides 17 and different families of composite and nanocomposite materials. [18][19][20][21] Recently, Shinde et al 22 demonstrated that successful self-assembly of MgH 2 nanoparticles in activated carbon led to the improvement of the physical and chemical behavior of the hydride phase for achieving reversible hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%